Highly dispersed gold nanoparticles anchoring on post-modified covalent organic framework for catalytic application - Zhang, Qing-Pu; Sun, Yu-ling; Cheng, Guang; Wang, Zhen; Ma, Hui; Ding, San-Yuan; Tan, Bien; Bu, Jian-hua; Zhang, Chun (Chemical engineering journal (Lausanne, Switzerland : 1996), 2020)
[Display omitted] •Sulfur-containing covalent organic framework (S-COF) was synthetized by post-modification strategy.•COF-supported Au NPs (Au-S-COF) has narrow size distribution (4.2 ± 1.2 nm) and high distribution density.•Au-S-COF exhibits excellent heterogeneous catalytic activity, stability and recyclability. Post-modification strategy was used to synthesize sulfur-containing covalent organic framework (S-COF) by thiol-ene “click” reaction from a propenyl-functionalized COF (A-COF). Furthermore, the obtained S-COF was used as matrix to successfully prepare COF-supported Au NPs (Au-S-COF) with narrow size distribution (4.2 ± 1.2 nm) and high distribution density, which shows excellent catalytic activities in reduction of 4-nitrophenol with remarkable stability and recyclability. In the Au-S-COF heterogeneous catalytic system, the strong anchoring ability between Au NPs and sulfur-containing groups over COF’s surface enhance the binding of Au NPs with COFs to maintain the dispersity of NPs and their catalytic activity for long-term performance.